Trends in popularity of some morphological traits of purebred dogs in Australia. Issue 1 (December 2016) - Teng, Kendy; McGreevy, Paul; Toribio, Jenny-Ann; Dhand, Navneet
Abstract Background The morphology of dogs can provide information about their predisposition to some disorders. For example, larger breeds are predisposed to hip dysplasia and many neoplastic diseases. Therefore, longitudinal trends in popularity of dog morphology can reveal potential disease pervasiveness in the future. There have been reports on the popularity of particular breeds and behavioural traits but trends in the morphological traits of preferred breeds have not been studied. Methods This study investigated trends in the height, dog size and head shape (cephalic index) of Australian purebred dogs. One hundred eighty-one breeds derived from Australian National Kennel Council (ANKC) registration statistics from 1986 to 2013 were analysed. Weighted regression analyses were conducted to examine trends in the traits by using them as outcome variables, with year as the explanatory variable and numbers of registered dogs as weights. Linear regression investigated dog height and cephalic index (skull width/skull length), and multinomial logistic regression studied dog size. Results The total number of ANKC registration had decreased gradually from 95, 792 in 1986 to 66, 902 in 2013. Both weighted minimal height (p =  0.014) and weighted maximal height (p <  0.001) decreased significantly over time, and the weighted cephalic index increased significantly (p <  0.001). The odds of registration of medium and small breeds increased by 5.3 % and 4.2 %, respectively, relative to large breeds (p <  0.001) and by 12.1 % and 11.0 %, respectively, relative to giant breeds (p <  0.001) for each 5-year block of time. Conclusions Compared to taller and larger breeds, shorter and smaller breeds have become relatively popular over time. Mean cephalic index has increased, which indicates that Australians have gradually favoured breeds with shorter and wider heads (brachycephalic). These significant trends indicate that the dog morphological traits reported here may potentially influence how people select companion dogs in Australia and provide valuable predictive information on the pervasiveness of diseases in dogs.